Investigation of electricity generation performance of grape marc in membrane-less microbial fuel cell - Taskan, Banu (Yildiz Technical University, 2021)
Grapes are among the most widely grown fruits globally, with a third of the overall production used in winemaking. Both red and white winemaking processes generate significant amounts of solid organic waste such as grape marc that requires proper disposal. Grape marc, a natural plant product containing abundantly lignocellulosic compounds, is a promising raw material for production of renewable energy. In this study, the grape marc was used as an anode nutrient in the membrane-less microbial fuel cell (ML-MFC) system, and the electricity generation capacity of the grape marc as an environmentally friendly energy source was investigated in detail. The maximum power density produced in the ML-MFC reactor was determined as 274.9 mW m-2, and the total internal resistance was 309.5 ?. Cyclic voltammetry results showed the presence of electroactive microorganisms on the surface of the anode electrode provided a high biological activity. The presence of elliptical and round-shaped microorganisms on the anode electrode surface was observed. Quantitative polymerase chain reaction (qPCR) analyzes have shown that grape marc supports bacterial growth on the electrode surface. © Yildiz Technical University, Environmental Engineering Department. All rights reserved.
Keywords: electricity generation; Grape marc; membrane-less microbial fuel cell (ML-MFC); microbial analysis